2019
DOI: 10.1108/tc-08-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of perpetrators of filicide participating in treatment within a prison therapeutic community

Abstract: Purpose The purpose of this paper is to explore the treatment experiences of adult male perpetrators of filicide within prison therapeutic communities (TCs). Design/methodology/approach Participants took part in semi-structured interviews in order to capture their treatment experiences. The data were analysed using interpretative phenomenological analysis. Findings Five superordinate themes (therapeutic process; acceptance; insight; relationships; and barriers) and ten subordinate themes were identified. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…‘I think what you’re in for has a lot to do with how you’re treated’, he concluded. These sorts of subtle, non-physically violent targeting practices were briefly mentioned by Jacobs and Shuker (2019) in their study on men convicted of killing children but were a key theme to come out of the interviews conducted as part of this research. In a mixed TC, therefore, lateral power was uniquely funnelled via TC processes, which is a key difference to lateral power described by Ievins (2020) in a single-offence penal setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…‘I think what you’re in for has a lot to do with how you’re treated’, he concluded. These sorts of subtle, non-physically violent targeting practices were briefly mentioned by Jacobs and Shuker (2019) in their study on men convicted of killing children but were a key theme to come out of the interviews conducted as part of this research. In a mixed TC, therefore, lateral power was uniquely funnelled via TC processes, which is a key difference to lateral power described by Ievins (2020) in a single-offence penal setting.…”
Section: Discussionmentioning
confidence: 99%
“…They are a niche but by no means insignificant group, as research has found that a significant minority of men with sexual offences also had histories of abuse (Jespersen et al, 2009;Seto and Lalumiere, 2010;Garbutt, 2018). It is worth noting that although this article focuses on a very specific group of residents, the themes discussed here provide an insight into TC's moral and power-laden world more broadly and can also be applied to other groups within penal settings, such as men convicted of killing children (see Jacobs and Shuker, 2019). Although the fieldwork was conducted in the UK, penal TCs of the type discussed here exist across the world, making this article of interest to academics and practitioners in other countries.…”
Section: Literature Reviewmentioning
confidence: 99%